2013
DOI: 10.1103/physrevlett.110.203905
|View full text |Cite
|
Sign up to set email alerts
|

Midfield Wireless Powering of Subwavelength Autonomous Devices

Abstract: We obtain an analytical bound on the efficiency of wireless power transfer to a weakly coupled device. The optimal source is solved for a multilayer geometry in terms of a representation based on the field equivalence principle. The theory reveals that optimal power transfer exploits the properties of the midfield to achieve efficiencies far greater than conventional coil-based designs. As a physical realization of the source, we present a slot array structure whose performance closely approaches the theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 26 publications
5
76
0
2
Order By: Relevance
“…It can be shown that transfer is maximized by correctly setting (i) the resonant frequencies of the source ω S and receiver ω C and (ii) the rate of energy extraction by the load γ L . In the weak coupling regime, it can be shown that the impedance-matching conditions are simply ω = ω S = ω C and γ L = γ C , where ω is the operating frequency and γ C the rate of energy loss at the receiver structure [26]. In the strong-coupling regime, the matching conditions differ by a correcting term dependent on the coupling strength due to mode-splitting [19].…”
Section: Coupled Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be shown that transfer is maximized by correctly setting (i) the resonant frequencies of the source ω S and receiver ω C and (ii) the rate of energy extraction by the load γ L . In the weak coupling regime, it can be shown that the impedance-matching conditions are simply ω = ω S = ω C and γ L = γ C , where ω is the operating frequency and γ C the rate of energy loss at the receiver structure [26]. In the strong-coupling regime, the matching conditions differ by a correcting term dependent on the coupling strength due to mode-splitting [19].…”
Section: Coupled Structuresmentioning
confidence: 99%
“…The design space, however, is too vast to exhaustively search with full-field electromagnetic simulations. To begin, the field equivalence principle can be invoked to reduce the dimensionality of the search space [26]. The principle is applied by drawing a plane between the surface of the body and the volume outside of the body where sources are allowed to exist.…”
Section: Optimal Energy Transfer Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, source structures that exploit the characteristics of the midfield to significantly improve the power transfer efficiency were analytically solved [7,8]. For the layered medium configuration shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For the layered medium configuration shown in Fig. 1, the equivalence principle in electromagnetic theory ensures that the optimal efficiency obtained in [8] bounds the efficiency attainable by any physical realization of the source. The maximum efficiency was shown to be a function of the dielectric property of the tissue, distance between the source and receiver (z f ), and orientation (θ) of the receiver coil.…”
Section: Introductionmentioning
confidence: 99%